2022
DOI: 10.1038/s41467-022-33738-3
|View full text |Cite
|
Sign up to set email alerts
|

Controllable DNA hybridization by host–guest complexation-mediated ligand invasion

Abstract: Dynamic regulation of nucleic acid hybridization is fundamental for switchable nanostructures and controllable functionalities of nucleic acids in both material developments and biological regulations. In this work, we report a ligand-invasion pathway to regulate DNA hybridization based on host–guest interactions. We propose a concept of recognition handle as the ligand binding site to disrupt Watson–Crick base pairs and induce the direct dissociation of DNA duplex structures. Taking cucurbit[7]uril as the inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…After examining these biochemical features of the crosslinked HHR, we then applied this chemically modified ribozyme to human cells to check its performance as a genesilencing tool. In order to explicitly monitor its efficiency, we first utilized this HHR to target the destabilized EGFP gene in the lentivirus-infected HEK293T cell line (HEK293T-d2EGFP), 45 so that the RNAi effects could be timely and directly observed from the changes of fluorescence signals (Figure 5A). Slightly different from the cross-linked HHR constructed for biochemical assays, we prolonged the length of Stem III (∼10 bp, depending on the sequence context) to ensure its stable binding against the RNA substrate under the cellular conditions (Figure 5B).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…After examining these biochemical features of the crosslinked HHR, we then applied this chemically modified ribozyme to human cells to check its performance as a genesilencing tool. In order to explicitly monitor its efficiency, we first utilized this HHR to target the destabilized EGFP gene in the lentivirus-infected HEK293T cell line (HEK293T-d2EGFP), 45 so that the RNAi effects could be timely and directly observed from the changes of fluorescence signals (Figure 5A). Slightly different from the cross-linked HHR constructed for biochemical assays, we prolonged the length of Stem III (∼10 bp, depending on the sequence context) to ensure its stable binding against the RNA substrate under the cellular conditions (Figure 5B).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Although the present study developed guest-modified adenosine derivatives, Xiao et al reported the formation of a re-versible base pair via host-guest interaction. 48 They attached guest moieties on the amino group of adenosine and cytidine through the C1 linker and demonstrated the reversible duplex formation using CB [7]. However, their nucleosides (e.g., A AD ) inherently destabilized the duplex regardless of the host-guest interaction (Figure S14) and exhibited a low affinity for complexation with CB [7].…”
Section: Structural Refinement To Tune the Kinetics Of The Reversible...mentioning
confidence: 99%
“…Supramolecular polymeric networks (SPNs) are polymeric networks constructed by both covalent and noncovalent interactions. , SPN-based materials combine the advantages of both covalent and noncovalent polymers through efficient functionalization, and they have a wide range of applications. The dynamic noncovalent supramolecular interactions in the SPNs endow the corresponding materials with high processability and excellent stimulus-responsiveness. Among the numerous supramolecular interactions, the outstanding selectivity and tunability make the host–guest interactions one of the widely studied topics in supramolecular chemistry. There are many macrocycle-based host–guest systems, such as crown ethers, cyclodextrins, , cucurbit­[n]­urils, , pillararenes, , calixarenes, heteracalixaromatics, corona­[n]­arenes, and beltarenes . Among them, crown ethers, the first generation of macrocyclic hosts, play a key role in the development of host–guest and supramolecular chemistry.…”
Section: Introductionmentioning
confidence: 99%